Airports’ role and operations in the international environment - Kalakou, S. (Industry, innovation and infrastructure, 2019)
An airport is a set of facilities, that comprises of buildings, runways, apron areas, roads and space connectors, and constitute the connector between surface and air transport. An airport is planned to serve passenger, cargo and aircraft movements in its facilities.